Pengembangan E-Modul Eksperimen Fisika Berbasis Project Based Learning - Puteri Hayati; Rosynanda Nur Fauziah (Departement of Mathematics Education, 2023)
This development research aims to determine whether the PjBL-based physics experiment e-module product is suitable for use by students. This research is a type of research and development (R&D) which refers to the four-D (4D) model which consists of 4 stages, namely Define, Design, Develop, and Disseminate. Feasibility data was taken by utilizing a questionnaire filled in by 2 material validators and 2 media validators. The average value of media validation by validator 1 is 3.841 and validator 2 is 3.300. While the average value of material validation by validator 1 is 3.25 and validator 2 is 3.75. So that with the average value that has been obtained and refers to the range of values <3.25 – 4, it can be concluded that the PjBL-based physics experiment e-module is stated to be very good and suitable for use by students.